A unique regional family interventions training programme. Issue 5 (10th September 2018) - Burbach, Frank R.; Sherbersky, Hannah; Whitlock, Ragni; Rapsey, Estelle H.; Wright, Kim A.; Handley, Rachel V.
Abstract : Purpose: The purpose of this paper is to describe the University of Exeter Family Interventions (FIs) training programme for the South West region which was commissioned as part of the NHS England Access and Waiting Times standards (A&WTS) initiative for early psychosis. This programme (10 taught days and 6 months of supervised practice) is designed to maximise implementation in practice. Design/methodology/approach: The programme introduces students to a flexible, widely applicable FI approach which integrates cognitive behavioural/psycho-educational and systemic approaches. It refreshes and develops CBT-based psycho-social intervention skills, so that clinicians feel confident to use them in family sessions and integrate these with foundation level family therapy skills. The approach facilitates engagement, and it is designed so that every session is a "mini intervention". This enables clinicians to offer standard NICE-concordant FI or a briefer intervention if this is sufficient to meet the particular needs of a family. Findings: This paper provides details of the regional training programme and evaluates the first four training courses delivered to nine early intervention in psychosis teams. It considers how a combination of training a critical mass of staff in each service, ongoing supervision, regional events to maintain skills and motivation to deliver FI, and the national and regional auditing of FI as part of the A&WTS all contribute to clinical implementation. Originality/value: The unique design of this programme maximises implementation in practice by virtue of its widely applicable integrated FI approach, the focus on ongoing skills development and by embedding it within regional and local service support structures.